Health and Environmental Pollution: A Literature Review - Yuniarti, Elsa; Exposto, Levi Anatolia S.M.; Dewata, Indang; Nugraha, Fitra Arya Dwi; Alfitri, Alfitri (Kesmas, 2024)
This study aimed to review various studies focusing on pollution that could adversely affect health, including sources, types, and mitigation efforts. The data used were obtained through a search on the Scopus website using the keywords "Health" AND "Pollution" from 2016 to 2023. Using these two keywords, 72 titles and abstracts of papers were successfully found. The results of this literature review were then analyzed with the assistance of NVivo 12 Pro, which grouped the findings based on their impact on health, reasons for pollution, types of pollution, and preventive measures. It was identified that the most common disease was respiratory disorder. One of the leading causes was vehicle combustion, emitting carbon monoxide due to the incomplete combustion of fossil fuels, such as petroleum and natural gas. This study also revealed that the dominant focus of those studies was on air and water pollution. These studies also indicated that solutions to pollution-causing diseases generally include using renewable fuels, waste management, public health literacy, and adopting electric vehicles.